Adenoid Cystic Carcinoma With Striking Tubular Hypereosinophilia: A Unique Pattern Associated With Nonparotid Location and Both Canonical and Novel EWSR1:MYB and FUS:MYB Fusions. (15th April 2023) - Weinreb, Ilan; Rooper, Lisa M.; Dickson, Brendan C.; Hahn, Elan; Perez-Ordonez, Bayardo; Smith, Stephen M.; Lewis, James S.; Skalova, Alena; Baněčková, Martina; Wakely, Paul E.; Thompson, Lester D.R.; Rupp, Niels J.; et al.
Abstract : The classification of salivary gland tumors is ever-evolving with new variants of tumors being described every year. Next-generation sequencing panels have helped to prove and disprove prior assumptions about tumors' relationships to one another, and have helped refine this classification. Adenoid cystic carcinoma (AdCC) is one of the most common salivary gland malignancies and occurs at all major and minor salivary gland and seromucous gland sites. Most AdCC are predominantly myoepithelial and basaloid with variable cribriform, tubular, and solid growth. The luminal tubular elements are often less conspicuous. AdCC has largely been characterized by canonical MYB fusions, with MYB::NFIB and rarer MYBL1::NFIB . Anecdotal cases of AdCC, mostly in nonmajor salivary gland sites, have been noted to have unusual patterns, including squamous differentiation and macrocystic growth. Recently, this has led to the recognition of a subtype termed "metatypical adenoid cystic carcinoma." Another unusual histology that we have seen with a wide range of architecture, is striking tubular hypereosinophilia. The hypereosinophilia and luminal cell prominence is in stark contrast to the vast majority of AdCC that are basaloid and myoepithelial predominant. A total of 16 cases with tubular hypereosinophilia were collected, forming morular, solid, micropapillary, and glomeruloid growth, and occasionally having rhabdoid or Paneth-like cells. They were subjected to molecular profiling demonstrating canonical MYB::NFIB (5 cases) and MYBL1::NFIB (2 cases), as well as noncanonical EWSR1::MYB (2 cases) and FUS::MYB (1 case). The remaining 6 cases had either no fusion (3 cases) or failed sequencing (3 cases). All cases were present in nonmajor salivary gland sites, with seromucous glands being the most common. These include sinonasal tract (7 cases), laryngotracheal (2 cases), external auditory canal (2 cases), nasopharynx (1 case), base of tongue (2 cases), palate (1 case), and floor of mouth (1 case). A tissue microarray of 102 conventional AdCC, including many in major salivary gland sites was examined for EWSR1 and FUS by fluorescence in situ hybridization and showed that these novel fusions were isolated to this histology and nonmajor salivary gland location. In summary, complex and striking tubular hypereosinophilia and diverse architectures are present within the spectrum of AdCC, particularly in seromucous gland sites, and may show variant EWSR1/FUS :: MYB fusions.